Indonesia Foreign Policy Update: rough waves ahead in the Indo-Pacific - I Gusti Bagus Dharma Agastia (AEGIS : Journal of International Relations, 2018)
Situated in a highly dynamic region at the crossroads of the Pacific and Indian Ocean, Indonesia’s foreign policy has long been influenced by both international and domestic factors. In light of these changes, we firstly look at the development of Indonesia’s external environment. This discussion centres on the dynamics in the Indo-Pacific between the major powers, specifically their outlooks, approaches, and interests in the region. Next, we examine Indonesia’s domestic dynamics, particularly those related to the progress of the development of the Global Maritime Fulcrum (GMF). In this section, we will discuss the process of naval modernization and an update of national political dynamics as the 2019 Presidential Elections loom closer. Finally, we examine the progress of Indonesia’s bilateral and multilateral cooperation.